A Unique Case: Solitary Fibrous Tumor of the Mandible - Stylianos N Zanakis; Megas F (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2017)
Solitary fi brous tumors (SFTs) were fi rstly reported in the pleura by Klemperer and Rabin [1], in 1931. These tumors are rare lesions and most commonly arise in the thoracic cavity [2]. Most of them occur as slow-growing painless masses. Rarely, larger tumors may be a source of paraneoplastic syndromes such as hypoglycemia owing to the production of insulinlike growth factor [3,4]. SFT is a mesenchymal neoplasm, previously nomenclatured as localized benign mesothelioma, submesothelioma, or localized fi brous tumor of the pleura [5]. It is now recognized that this may also occurs in extrapleural sites. Recently, however, SFT has been shown to originate from ubiquitous interstitial stem cells in various human tissues and its histopathological criteria have been established by the aid of immunohistochemistry [6]. SFTs arising in the soft tissue of the head and neck account for approximately 10% of all cases [7]. Those occurring in the oral cavity accounts for 3% of all head and neck cases [5]. In the present report we describe the occurrence of a SFT case in the angle region of the mandible. This is the fi rst case report of a SFT arising in the mandible.